Transfusion-transmitted AIDS with blood negative for anti-HIV and HIV-antigen - Ampaiwan Chuansumrit (2018)
A four-year-old boy who was diagnosed with Glanzmann's thrombasthenia received supportive treatment and desmopressin for his bleeding episodes. He seldom received blood components, except for platelet concentrates, due to severe bleeding. He was exposed to 18 routine donors and 2 plateletpheresis donors who were negative for human immunodeficiency virus (HIV) antigen and anti-HIV upon screening. At the age of 3 years and 9 months (4.5 months after the transfusion of platelet concentrate), he developed full-blown AIDS and died from circulatory failure 3 months later. The source of HIV transmission was identified as 1 donor who developed anti-HIV 3 months after the last donation. The rather short incubation time of AIDS in this case was attributed to a large inoculum of HIV virus in the 'window period' of infectivity of the newly infected donor. This case illustrates transfusion-transmitted HIV leading to AIDS, even though HIV antigen and anti-HIV screening tests were negative.